Understanding Atherosclerosis: Pathophysiologic Insights and Primary Prevention to Mitigate Coronary Events - Abdul Hakim Alkatiri; Jasmine Ibtisimah AlkatirI; William Suciangto; Iskam Syawal; Andriany Qanita (Physical Activity, Nutrition and Health Sciences Journal, 2025)
Atherosclerosis represents the fundamental pathological process underlying ischemic heart disease, particularly acute coronary syndrome, and remains a major cause of cardiovascular morbidity and mortality worldwide. Its development is driven by a complex interplay of endothelial dysfunction, lipid deposition, inflammatory activation, and fibrous plaque formation, culminating in plaque rupture and subsequent coronary flow obstruction. In this paper, we comprehensively explore the pathophysiological mechanisms of atherosclerosis and discuss potential preventive strategies aimed at attenuating its progression and reducing the burden of ischemic heart disease.